Music Learning with Massive Open Online Courses (MOOCs) - L. Steels (ed.) (The Future of Learning, 2015)
"Massive Open Online Courses, known as MOOCs, have arisen as the logical consequence of marrying long-distance education with the web and social media. MOOCs were confidently predicted by advanced thinkers decades ago. They are undoubtedly here to stay, and provide a valuable resource for learners and teachers alike. This book focuses on music as a domain of knowledge, and has three objectives: to introduce the phenomenon of MOOCs; to present ongoing research into making MOOCs more effective and better adapted to the needs of teachers and learners; and finally to present the first steps towards 'social MOOCs', which support the creation of learning communities in which interactions between learners go beyond correcting each other's assignments. Social MOOCs try to mimic settings for humanistic learning, such as workshops, small choirs, or groups participating in a Hackathon, in which students aided by somebody acting as a tutor learn by solving problems and helping each other. The papers in this book all discuss steps towards social MOOCs; their foundational pedagogy, platforms to create learning communities, methods for assessment and social feedback and concrete experiments. These papers are organized into five sections: background; the role of feedback; platforms for learning communities; experiences with social MOOCs; and looking backwards and looking forward. Technology is not a panacea for the enormous challenges facing today's educators and learners, but this book will be of interest to all those striving to find more effective and humane learning opportunities for a larger group of students."